Secure broadcast for inter vehicle communications. (15th November 2007) - Durresi, A.; Durresi, M.; Bulusu, V.; Barolli, L.
In the near future, radio communication among vehicles and fixed infrastructure on highways will make driving more comfortable and specially safer by offering information which would prevent accidents by giving early warning signals. In such communications, security of service becomes a very critical issues. We propose a security protocol which would allow secure non-refutable broadcasts among vehicles. Key distribution for this protocol is performed by using both roadside base stations and threshold cryptography. This paper also addresses the privacy concerns of using a security protocol which needs strong authentication.